RNA-lipid nanoparticle therapeutics for women’s health - Nomani, Alireza; Saraswat, Aishwarya; Zhang, Yu; Parenky, Ashwin C.; Kuo, Chun-Tien Jimmy; Brown, Heather; Hartford, Suzanne; Rayaprolu, Bindhu; Singh Bhupender Bhalla, Amardeep; Shameem, Mohammed (Frontiers in Nanotechnology, 2025)
Ribonucleic acid-lipid nanoparticle (RNA-LNP) therapeutics, a powerful nanomedicine platform, have already demonstrated their efficacy in diverse applications. Their improved stability and efficacy are exemplified by successful and rapid launch of mRNA vaccines, as well as marketed siRNA drug product. Beyond infectious diseases, RNA-LNPs show promise in addressing unmet needs in women’s health, for instance, gynecologic cancers (e.g., ovarian, cervical) and novel treatments for conditions such as osteoporosis, endometriosis, and congenital disorders. However, important challenges persist, including off-target effects, immunogenicity, and potential risks and ethical issues in their application for pregnant or lactating women. This review summarizes current key preclinical and clinical progress, discusses targeting strategies of LNPs (e.g., active and passive delivery), and presents current knowledge on RNA-LNP safety in pregnant and non-pregnant women and neonates as vulnerable populations. As RNA-LNP technologies evolve – with relevant preclinical animal models, next-generation RNA platforms and improved lipid chemistries – they can hold significant potential for transforming care in women’s health through safer, effective, personalized, and innovative curative interventions.